Implementation of Family Development Tasks and Severity of ARI in Toddlers - Rahmawati, Wenny; Satiti, Ika Arum Dewi (Universitas Tribhuwana Tunggadewi, 2025)
Acute Respiratory Infection (ARI) refers to an infection targeting the human respiratory passages, predominantly affecting children between the ages of 1 and 5 years. Improperly managed ARI condition can result in worsening nutritional conditions, secondary infections, stunted growth, and development. The family plays an important role in efforts to prevent ARI and its complications. When the family gets better at Providing family health services, the level of ARI that occurs in the family becomes less severe. The current study investigates the link between family health tasks and severity of Acute Respiratory Infections (ARI). An observational approach was utilized in this study with a retrospective design. The activities were conducted during the period June-August 2022 at the Dinoyo Community Health Center, Malang City. Purposive sampling was used resulted in 57 samples experiencing ARI. The instruments for both variables were assessed through questionnaires The hypothesis was tested using a chi-square test. The result show mothers who had poor family development tasks had a severity level of severe ARI of 38.6%; mothers in charge of family development had mild ARI in 15.8% of cases and moderate ARI in an estimated 22.8% of cases. The results obtained from the Chi-Square Test have a p-value = 0.000. This study reveals a significant correlation between family task performance and ARI severity in toddlers. Mothers who demonstrate poor achievement in family developmental tasks are more likely to have children experiencing higher severity of ARI.